Women on Boards and CSR Performance: The Role of Gender Diversity and Executive Competencies in OECD Countries - AROUS, Islem; Jbouri, Hayfaa; HAMAD, Salah BEN (Journal of Cultural Analysis and Social Change, 2026)
The possible influences of gender diversity on corporate social responsibility (CSR) have been the subject of several studies in recent years, but no work has yet analysed this relationship on OECD firms. Our study examines how board diversity and female executive competencies influence corporate social responsibility (CSR) performance across OECD firms from 2017 to 2022. Drawing on stakeholder and upper echelons theories, we argue that diverse and competent leadership enhances sustainable governance outcomes. Using dynamic panel GMM estimation and Bayesian NUTS regression for robustness, we provide consistent empirical evidence on the governance determinants of CSR. Results show that ESG pillars jointly drive long-term sustainability performance. Gender and cultural diversity display a positive, though moderate, association with CSR, supporting the view that inclusive boards strengthen stakeholder orientation. More importantly, female executives’ human capital significantly improves ESG outcomes.